2014
DOI: 10.1088/0957-4484/25/5/055207
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of polarization sensitivity in closely stacked trilayer InAs/GaAs quantum dots induced by overgrowth dynamics

Abstract: Abstract:Tailoring electronic and optical properties of self-assembled InAs quantum dots (QDs) is a critical limit for the design of several QD-based optoelectronic devices operating in the telecom frequency range. We describe how a fine control of the strain-induced surface kinetics during the growth of vertically-stacked multiple layers of QDs allow to engineer their self organization process. Most noticeably, the present study shows that the underlying strain field induced along a QD stack can be modulated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Therefore we have ignored this effect in our simulations. However, our recent studies 46,47 have indicated that the In-Ga intermixing has a minor impact on the confinements and symmetries of the electron and hole wave functions for the single and trilayered QD systems. Consequently, we expect that the presented physical insights will remain valid in the presence of weak In-Ga intermixings.…”
Section: Theoretical Frameworkmentioning
confidence: 96%
“…Therefore we have ignored this effect in our simulations. However, our recent studies 46,47 have indicated that the In-Ga intermixing has a minor impact on the confinements and symmetries of the electron and hole wave functions for the single and trilayered QD systems. Consequently, we expect that the presented physical insights will remain valid in the presence of weak In-Ga intermixings.…”
Section: Theoretical Frameworkmentioning
confidence: 96%